Evaluation of growth and yield performance of year round watermelon (Citrullus lanatus): Growth and yield of year round watermelon (South Asian Journal of Agriculture, 2023)
An experiment was conducted during July 2021 at Bangabandhu Academy for Poverty Alleviation and Rural Development (BAPARD) agricultural farm to evaluate growth and yield performance of four year round watermelon (Citrullus lanatus) viz. Golden Crown, Black Boss, Sweet Black and Karishma. The experiment was laid out in Randomized Complete Block Design (RCBD) with four replications. Data were collected on selected growth and yield attributes. Days to first male and female flowering and ratio of male and female flower were almost similar for all varieties. The highest number of male and female flower was recorded in Golden Crown 50.0 and 12.67, respectively. As a result, the maximum number of fruit setting (6.08) was found in Golden Crown and the minimum in Sweet Black (2.92). The length of fruit was ranged from 17.42- 21.43cm. The maximum diameter of fruit was found in Golden Crown (13.68cm) and the minimum in Black Boss (10.6cm). The weight of individual fruit was observed from 2.34 kg to 2.95 kg which was statistically identical among the varieties. The maximum yield per plant was in Golden Crown (17.73 kg) due to highest number of fruit setting. Finally, it might be concluded that the growth and yield performance of Golden Crown were better in compare to other tested varieties.South Asian J. Agric., Vol. 9, No.1&2, 2022-‘23: 80-85